De l’interopérabilité à la réutilisabilité des éditions électroniques - Ioana Galleron; Fatiha Idmhand (Humanités Numériques)
While the quality and the relevance of the digital scholarly edition (DSE) have been repeatedly discussed and led to the formulation of various recommendations and grids of analysis, the possible “re-uses” of the published texts have less often been taken into account as a principle guiding the activity of the editorial team. This paper starts from the assumption that this aspect is essential in DSEs, in spite of the difficulties it raises. The scientific objectives of the editor are, indeed, sometimes in conflict with the expectations of the future users. The paper presents three modalities for finding a balance between the needs and wishes of the editorial team, and those of the wider scholarly public: a preliminary survey, an approach from a theoretical standpoint, or a mix of both. In the last part, the paper reflects on the re-uses of a text from the point of view of John Unsworth’s “scholarly primitives”.